Efficacy of Zulu indigenous games in enhancing perceptual-motor skills in pre-schoolers: a qualitative study of two informal settlements in Kwa Zulu Natal - Brand, Nicolette (School of Education, 2025)
An increasing number of learners entering formal schooling lack essential learning readiness skills, such as perceptual-motor development, and are therefore underprepared for learning. Although indigenous games have the potential to enhance perceptual-motor development, there is a paucity of research on the use of indigenous games for school readiness among Grade R learners. This study evaluates cognitive and perceptual-motor skills in Zulu indigenous games, drawing on Vygotsky's Sociocultural Theory, Piaget's Cognitive Development Theory, and Bronfenbrenner's Ecological Systems Theory, to enhance the school readiness of Grade R learners in a resource-constrained context. Data was collected using a qualitative methodology and analysed within the interpretive paradigm, incorporating interviews, observations, and field notes. The study employed structured and semi-structured interviews to investigate the educational characteristics of Zulu Indigenous games from the community's perspective and adults' perceptions of their benefits for holistic development. Participants aged twenty to thirty from two regions recognised the beneficial effects of Zulu Indigenous games on physical, cognitive, and social abilities. However, they indicated that demanding work schedules, particularly in corporate environments in Durban, limited their participation in traditional games. Participants reported primarily using English at work and leisure, influencing their cultural practices. Despite these challenges, there is hope that incorporating traditional games into school curricula will preserve cultural heritage for future generations. Concerns about adequate teacher training were expressed, particularly among younger educators unfamiliar with these games. Physical and group interactions, skill development, cultural history, and group dynamics emerged as key themes, emphasising the multifaceted benefits of Zulu Indigenous games in promoting community bonds, personal growth, and cultural preservation. The research concludes that incorporating Zulu indigenous games with educational value from Zulu culture into the school curriculum can be extremely beneficial for addressing the impact of delayed perceptual motor development on school readiness and promoting holistic child development. By incorporating Zulu indigenous games into the curriculum, schools can simultaneously promote cultural inclusivity, respect, and appreciation while fostering the perceptual-motor development of children.